A Framework for the Integration of Behavioral Health and Oral Health in Predoctoral Dental Education - Tamanna Tiwari; Cameron L. Randall (Taylor & Francis Group, 2024)
ABSTRACTBackground Oral health and mental health are connected in complex and important ways. Epidemiological trends in oral health and mental health, as well as trends in approaches to healthcare and changes in health systems, underscore the need to teach predoctoral dental students about mental health and the broader concept of behavioral health.Objective This article introduces a framework for the integration of behavioral health and oral health (IBOH) in the predoctoral dental school curriculum. To describe the framework, the article includes a narrative review of both primary studies and reports by government agencies and health-related nonprofit organizations.Conclusion The framework comprises three domains - education, organization, and community - with a commitment to lifelong learning at the center. The education domain includes a curriculum on the mental health and oral health connection, patient behavior and health promotion, and dentist-patient interaction. The organization domain includes a supportive organizational environment. The community domain includes community priorities and engagement. Case examples of IBOH in predoctoral dental school curricula and beyond are presented to illustrate application of the framework. A call to action describes key points dental schools should consider as they develop and implement IBOH in the predoctoral curriculum.Practical Implications Practically speaking, IBOH in predoctoral dental education will prepare future dentists to provide comprehensive, person-centered care that is responsive to the oral health-relevant behavioral health needs of patients. Further, with an IBOH curriculum, dental school graduates will have the knowledge and skills necessary to work in integrated healthcare systems and on interprofessional teams.